Authenticated key exchange under bad randomness - YANG, Guomin (Institutional Knowledge at Singapore Management University, 2011)
We initiate the formal study on authenticated key exchange (AKE) under bad randomness. This could happen when (1) an adversary compromises the randomness source and hence directly controls the randomness of each AKE session; and (2) the randomness repeats in different AKE sessions due to reset attacks. We construct two formal security models, Reset-1 and Reset-2, to capture these two bad randomness situations respectively, and investigate the security of some widely used AKE protocols in these models by showing that they become insecure when the adversary is able to manipulate the randomness. On the positive side, we propose simple but generic methods to make AKE protocols secure in Reset-1 and Reset-2 models. The methods work in a modular way: first, we strengthen a widely used AKE protocol to achieve Reset-2 security, then we show how to transform any Reset-2 secure AKE protocol to a new one which also satisfies Reset-1 security.